Do macroprudential policy instruments reduce the procyclical impact of capital ratio on bank lending? Cross-country evidence - Małgorzata Olszak; Sylwia Roszkowska; Iwona Kowalska (Baltic Journal of Economics, 2019)
In this paper, we ask about the capacity of macroprudential policies to reduce the procyclical impact of capital ratio on bank lending. We focus on aggregated macroprudential policy measures and on individual instruments and test whether their effect on the association between lending and capital depends on bank size. Applying the GMM 2-step Blundell and Bond approach to a sample covering over 60 countries, we find that macroprudential policy instruments reduce the procyclical impact of capital on bank lending during both crisis and non-crisis times. This result is stronger in large banks than in other banks. Of individual macroprudential instruments, only borrower-targeted LTV caps and DTI ratio weaken the association between lending and capital and thus act countecyclically. Generally, with our study we are able to support the view that macroprudential policy has the potential to curb the procyclical impact of bank capital on lending and therefore, the introduction of more restrictive international capital standards included in Basel III and of macroprudential policies are fully justified.
Keywords: E32; G21; G28; G32; 330; Loan supply; capital ratio; procyclicality; macroprudential policy